Aspectos taxonómicos relativos al pejibaye (Bactris gasipaes H.B.K.) - Mora Urpí, Jorge (1981)
The controversial status of the genera Guillielma and Bactris under both of which the pejibaye palm (Bactris gasipaes H.B.K.) has been placed at one time or another is discussed briefly. It is still an open question if Guillielma should be maintained as some sort of a taxon. Also, a review is made of the names that at some time have been placed under Guillielma. Of the 14 specific names included under this genus, some are considered synonymous, some of these species probably lack enough affinity to be grouped together and it is very possible that other species exist which could be included in the genus and are not yet described. The possible hybrid origin of the cultivated pejibayes is al so briefly discussed.